An Analysis Of English Education Textbook For Sixth Grade Elementary Students - Saputra, Abyan Iza; Ambarwati, Evi Karlina (Jurnal Ilmiah Wahana Pendidikan, 2024)
Textbooks have given us a lot of opportunities and a chance to gain something new and teach proper material our students so they can be more confident and have courage on what they can do by using textbooks as their way to learn something new. But despite with lot of information and knowledge that textbooks can give to the students, we as a teacher also should known how to choose a good textbook based on the Regulation of the Minister of Education and Culture No. 8 the Year 2016, which said that every good textbook should’ve followed basic of UUD 1945 and also follow the value of Pancasila since it was also already had the appropriate framework of analysis for textbook evaluation purpose. So the analysis that will be conducted will focus on the relevance of materials that good for the students in sixth grade, the quality of materials, standards materials, and how good it’s the supporting material given in the textbook. With that, I hope after analyzing the textbook, it can show how appropriate material that used for students based on the Regulation of the Minister of Education and Culture No. 8 of the Year 2016.